Acoustic compatibilization material, preparation method thereof, loudspeaker module and electronic equipment
By loading the COF material on the hosting carrier of the porous structure, forming a multi-stage porous structure acoustic capacitance material, the problems of existing materials in the pore distribution and crystalline state are solved, and the low-frequency effect of the speaker and the mechanical properties of the material are significantly improved.
Patent Information
- Application Number
- CN202411672625.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing acoustic improvement materials cannot accurately control the distribution and direction of the pore structure during the preparation process, and the oxide materials cannot form crystalline substances, affecting the acoustic effect.
The acoustic capacitance-enhancing material with a perimeter structure is used to form a multi-stage porous structure by loading or embeding the coF material into the perimeter carrier of a perimeter structure, thereby improving the acoustic capacitance effect.
The adsorption and desorption ability of gas molecules is improved, the low frequency effect of the speaker is significantly improved, and the mechanical strength and compressive resistance of the material are improved.
Smart Images

Figure CN119529544A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of loudspeaker manufacturing, and in particular to an acoustic volume-increasing material and a preparation method thereof, a loudspeaker module and an electronic device. Background Art
[0002] COF material is one of the commonly used porous materials, but the water absorption and low-frequency improvement performance of COF material still need to be improved.
[0003] In the prior art, acoustically active articles can be made from inorganic agglomerates, which have an average size of 50 μm-2 mm and contain a network of carbon or silicon dioxide and metal oxide particles embedded in the network, which can reduce the resonant frequency of acoustic devices in the frequency range of 50 Hz to about 1500 Hz.
[0004] There is also existing technology for preparing virtual acoustic materials through emulsion in-situ synthesis methods. This type of method usually uses organic silica gel as a silicon source and adhesive, aluminum oxide, aluminum hydroxide, fumed silica, etc. as a structural regulator, and nano-micron-level carbon black as a porogen. The organic silica and other components are dissolved or dispersed evenly by a low-boiling point solvent, and then microspheres with a particle size range of 50μm-2mm are prepared by suspension polymerization in an aqueous phase system containing a surfactant. After high-temperature calcination in an aerobic environment to remove the porogen and hydrocarbon components, a white porous composite inorganic microsphere material is obtained. The microsphere product with a particle size range of 50μm-1000μm can greatly reduce the actual volume of the speaker without affecting its acoustic effect.
[0005] However, the above acoustic improvement materials have the following problems: In the above schemes, the raw materials for preparing the improvement materials are usually porous oxide materials such as aluminum oxide and carbon dioxide. These porous materials are formed by carbonizing organic carbon tissue in the presence or absence of oxygen to form a porous structure. The distribution of organic carbon in the carbonization process is uncontrollable, and the formation of pores is greatly affected by the distribution of organic carbon. Therefore, the above method cannot accurately control the distribution and direction of the pore structure. In addition, oxides such as aluminum oxide and silicon dioxide cannot form crystalline substances in the above preparation process, and there is a lack of regularly distributed pore structures inside these oxide structures. Summary of the invention
[0006] In order to solve the above problems, the purpose of the present invention is to provide an acoustic volume-increasing material and a preparation method thereof, a speaker module and an electronic device. The acoustic volume-increasing material has a multi-level pore structure, has a good acoustic volume-increasing effect, and can effectively improve the low-frequency effect of the speaker.
[0007] In order to achieve the above object, the present invention provides an acoustic volume-enhancing material, which includes a host carrier and a COF (covalent organic framework compound) material, wherein the host carrier has a pore structure, the pore structure includes mesopores and macropores, and the COF material is loaded and / or embedded in the pore structure of the host carrier;
[0008] The COF material has three-dimensional pores, the pore diameter of the three-dimensional pores in the COF material is not less than (greater than or equal to) 0.04 nm, and the pores are interconnected.
[0009] The above-mentioned acoustic volume-increasing material is a parasitic structure, and the COF material can form a parasitic structure by loading and / or embedding in the pore structure of the parasitic carrier. Because the COF material is loaded or embedded in the pore structure of the parasitic carrier, it provides support in the mesopores and macropores of the parasitic carrier, and the acoustic volume-increasing material obtained by the composite has higher mechanical strength than the parasitic carrier; at the same time, COF has a low relative atomic mass of its main elements and developed pores, so it will not have a significant effect on the density of the parasitic structure; in addition, the polar groups involved in the COF material can be combined with the hydroxyl groups in the porous carbon as the parasitic carrier, and the water absorption rate of the parasitic structure can be reduced while improving the binding force between COF and the carrier; the parasitic structure can make the pore structure in the parasitic carrier cooperate with the pore structure in the COF material, which can improve the adsorption and desorption ability of the acoustic volume-increasing material for gas molecules, thereby significantly improving the low-frequency effect. In addition, the acoustic volume-increasing material with a parasitic structure itself has a molded appearance and a suitable size, and there is no need to introduce a molding adhesive to mold the acoustic volume-increasing material.
[0010] In some specific embodiments, the compressive strength of the acoustic volume-enhancing material is greater than or equal to 0.1N; further, the compressive strength can reach above 1.4N.
[0011] In some specific embodiments, the density of the acoustic volume enhancement material is less than or equal to 0.8 g / cm 3 .
[0012] In some specific embodiments, the water absorption rate of the acoustic capacity-enhancing material is less than or equal to 11%, and further may be less than or equal to 5.0%.
[0013] In some specific embodiments, the specific surface area of the acoustic volume-enhancing material is 2500-2900 m 2 / g, further can be 2600-2900m 2 / g, further can be 2700-2900m 2 / g.
[0014] In the above-mentioned acoustic volume-enhancing materials, the host carrier generally has a porous structure, at least with mesopores and macropores. Among them, the mesopores can provide channels for the circulation of gas molecules, and can also be used for the adsorption and desorption of gas molecules; the macropores can be used to load or grow COF materials, and the macropores can also be used together with the mesopores to adsorb and desorb gas molecules to achieve a sound-absorbing effect, and cooperate with the porous material to achieve an acoustic volume-enhancing effect. In some specific embodiments, the pore size of the mesopores of the host carrier is 2nm-50nm, and the pore size of the macropores of the host carrier is usually 50nm-20μm.
[0015] In the above-mentioned acoustic volume-enhancing material, the host carrier may include a porous carbon material. Further, the porous carbon material may include one or a combination of two or more of carbonized coconut shell, soft carbon, hard carbon (such as lignite, etc.), carbon molecular sieve, functionalized activated carbon (such as alkaline-modified activated carbon), etc., and the functionalized activated carbon may include alkaline-modified activated carbon.
[0016] In the above acoustic volume enhancement material, the host carrier can withstand a temperature above 200° C., so that the host carrier can withstand the crystallization temperature and crystallization process of the COF material, thereby preventing the structure of the host carrier from being affected by the crystallization process.
[0017] Among the above-mentioned acoustic volume expansion materials, the COF material with a three-dimensional pore structure has a more developed pore structure. When the external pressure changes, it can quickly adsorb and desorb air, expand the virtual volume of the speaker for acoustic volume expansion, and thus improve the low-frequency acoustic effect.
[0018] In the above acoustic volume-enhancing material, the COF material has three-dimensional channels, and the channels are interconnected.
[0019] In the above-mentioned acoustic volume-enhancing material, the COF material has micropores and / or mesopores, and the pore size in the COF material is greater than or equal to 0.4 nm; and the pores are interconnected, so that gas molecules (mainly nitrogen molecules) can freely enter and exit the pores of the COF material to achieve an acoustic volume-enhancing effect.
[0020] In the above acoustic volume-enhancing materials, the COF material may have a higher specific surface area and a higher adsorption capacity for air. In some specific embodiments, the specific surface area of the COF material may reach 300 m 2 / g or more, and can further reach 400m 2 / g or above or 500m 2 / g or more, and can further reach 800m 2 / g or above.
[0021] In the above-mentioned acoustic volume-enhancing materials, the COF material used in the present invention generally has a higher degree of crystallinity, so the COF material of the present invention has a higher degree of structural order and more regularly distributed pores than the amorphous material. In some specific embodiments, the crystallinity of the COF material can reach more than 80%. The crystallinity is a relative crystallinity, which can be calculated based on the ratio of the total area of the crystallization peak to the total area of all the peaks (the sum of the areas of the crystallization peak and the amorphous peak), and the calculation formula is:
[0022] Crystallinity (%) = ∑A crystalline / (∑A crystalline +∑A amorphous ), where A crystalline is the area of the crystallization peak, A amorphous is the area of the amorphous peak.
[0023] In the above-mentioned acoustic volume-enhancing material, the COF has a three-dimensional channel connected by N construction nodes, N ≥ 4. Specifically, N can be 4, 6 or 8, that is, the COF can include a three-dimensional channel structure constructed by four-connected, six-connected, and eight-connected construction nodes. More specifically, the COF material includes but is not limited to one or a combination of two or more of COF-102, COF-103, COF-105, COF-108, COF-202, COF-300, COF-302, and COF-505.
[0024] According to a specific embodiment of the present invention, the mass ratio of the host carrier to the COF material can be 4:1-1:4, for example, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4 and other specific values and ranges with any two of the above specific values as endpoints. In some specific embodiments, the mass ratio of the host carrier to the COF material can be 2:1-1:2.
[0025] According to a specific embodiment of the present invention, the acoustic volume-increasing material can be used as a volume-increasing material in a loudspeaker. The acoustic volume-increasing material can expand the virtual volume in the loudspeaker and improve the low-frequency effect.
[0026] The present invention also provides a method for preparing the acoustic volume-increasing material, comprising immersing a host carrier in a solution of a COF material precursor, and crystallizing the solution to obtain the acoustic volume-increasing material; wherein the preparation method does not include a calcination step.
[0027] In the above preparation method, the COF material precursor is a COF mother solution, which contains raw materials for forming COF material.
[0028] In the above preparation method, the COF material precursor generally includes a reagent having an N-connected building node (or: a multi-connected building node reagent), N≥4, for example, N can be 4, 6 or 8. Specifically, the reagent having an N-connected building node can include a combination of two or more of tetrakis(4-boronic acid phenyl)methane, n-butylsilanetriol, tetrakis(4-phenylamino)methane, 3,3',5,5'-tetraaldehyde biphenyl, [1,1:3,1-terphenyl]-3,3,5,5-tetraaldehyde, aminotetraphenylporphyrin, 2,3,6,7,14,15-hexaaldehyde phenyltriptycene, tetrakis(4-pinacolylphenyl)methane, tetrakis(4-boronic acid phenyl)ethylene, and 3,3',5,5'-tetrakis(p-aminophenyl)-biphenyl.
[0029] In the above preparation method, the COF material precursor may further include a ligand, and the ligand reacts with a reagent having a node construction to form a COF. Specifically, the ligand may include p-phenylenediamine, terephthalaldehyde, terephthalimethanol, biphenylenediamine, biphenyldicarboxaldehyde, 1,4-diiodo-2,5-dimethylbenzene, 4,4-dibromo-2,2-bipyridine, 2,4,6-tris(4-aminophenyl)-1,3,5-triazine, 1,3,5-tris(4-ethynylphenyl)benzene, 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, tris(4-ethynylphenyl)amine, one or a combination of two or more thereof.
[0030] In the above preparation method, the particle size of the host carrier is usually controlled to be 30-50 mesh, such as 30-40 mesh.
[0031] In the above preparation method, before immersing the carrier in the solution of the COF material precursor, the above preparation method may include an operation of pre-treating the carrier.
[0032] When the host carrier is carbonized coconut shell, the pretreatment process may include: subjecting the host carrier to high temperature treatment at 450°C-800°C in a protective atmosphere for more than 2 hours (such as 4 hours). The protective atmosphere may be nitrogen, helium, etc. The pretreatment process will not have a significant effect on the distribution and orientation of the pores in the host carrier, but can reduce the amount of water adsorbed by the host carrier and fully carbonize the host carrier. The fully carbonized host carrier has a high degree of openness of the pores inside, close to full openness, and the porosity and surface area of the host carrier are also improved, which is beneficial to increase the load of the host carrier on the COF material. In some specific embodiments, the above-mentioned pretreatment may further include: before the high-temperature treatment, subjecting the host carrier to a first screening, ball milling, a second screening, and drying process.
[0033] In the above preparation method, when the host carrier is hard carbon, the pretreatment process of the host carrier may include: drying the hard carbon (lignite, etc.) to remove moisture and volatile components, carbonizing it at high temperature in a protective atmosphere (such as nitrogen or helium), the carbonization temperature may be 1500°C, the carbonization time may be 12 hours, crushing the carbonized product, screening it for the first time, ball milling it, screening it for the second time, drying it, and completing the pretreatment.
[0034] In the above pretreatment process, the particle size of the host carrier obtained after ball milling can reach 30-50 meshes, and the host carrier after ball milling can remove irregular edges and corners and present an ellipsoid or sphere. After the first screening, particles with a particle size of 20-40 meshes can be obtained, and after the second screening, particles with a particle size of 30-40 meshes can be obtained.
[0035] In the above preparation method, the crystallization conditions can be adjusted according to the type and degree of crystallization of the COF material. The crystallization conditions can be 80°C-160°C for 36h-120h. Generally, the crystallization temperature does not exceed 200°C (i.e., the crystallization temperature is less than or equal to 200°C) to avoid changes in the pore structure of the host carrier during the crystallization process.
[0036] According to a specific embodiment of the present invention, the above preparation method may include:
[0037] Step 1, pretreatment: the parasitic carrier is screened for the first time, and then ball-milled, during which the shape of the carrier tends to be regular (such as spherical or ellipsoidal); the parasitic carrier after ball milling is screened for the second time to obtain a parasitic carrier with a particle size of 30-50 mesh, and dried (the condition can be dried at 60° C. for 12 hours); the parasitic carrier after drying is subjected to a high temperature treatment at 450-800° C. for more than 2 hours (for example, 4 hours) to obtain a pretreated parasitic carrier;
[0038] Step 2: immerse the pretreated host carrier in the solution of the COF material precursor, stir to make the solution fully wet the host carrier, and crystallize at 80°C-160°C for 36h-120h to obtain the acoustic volume enhancement material. In step 2 of the above preparation process, high temperature treatment such as calcination is not performed.
[0039] The present invention also provides a speaker module, which includes the above-mentioned acoustic volume-increasing material. In some specific embodiments, the acoustic volume-increasing material can be filled, sprayed or coated at any position of the speaker module to achieve multiple functions such as sound absorption and shock absorption.
[0040] According to a specific embodiment of the present invention, the acoustic volume-increasing material can be filled inside the speaker module. More specifically, a speaker can be provided in the resonance cavity of the speaker module, and the acoustic volume-increasing material is filled in the resonance cavity of the speaker module. By filling the acoustic volume-increasing material in the inner cavity of the speaker module, the adsorption and desorption capacity of air can be improved, the virtual volume of the speaker can be expanded, and the effect of improving low frequency can be achieved.
[0041] The appearance of the acoustic volume-enhancing material provided by the present invention can be adjusted according to actual needs (such as the shape of the cavity filled by the material), and can be granular, block, sheet, etc. For example, the appearance of the acoustic volume-enhancing material can be changed by bonding and other means to present a granular, block, sheet, etc. shape.
[0042] The present invention also provides an electronic device, which includes the above-mentioned speaker module. In some specific embodiments, the electronic device can be a smart phone, a smart watch, a tablet computer, smart glasses, VR glasses, a smart speaker or a laptop computer (especially a thin and light laptop computer), etc.
[0043] According to a specific embodiment of the present invention, the electronic device is provided with a sound output opening and a sound output channel, and the speaker module is acoustically coupled with the sound output opening through the sound output channel.
[0044] According to a specific implementation of the present invention, the speaker module is integrally formed with the electronic device; or, the electronic device further includes a casing, and the speaker module is disposed in an internal space formed by the casing.
[0045] The beneficial effects of the present invention include:
[0046] The acoustic volume-increasing material provided by the present invention combines the advantages of light weight and large air adsorption of the carrier material, and the advantages of regular pores and pore structure of the COF material by loading the COF material in the porous structure of the host carrier. Because the COF material is loaded or embedded in the pore structure of the carrier, it provides support in the mesopores and macropores, and has higher mechanical strength than the host carrier; at the same time, COF does not significantly increase the density of the host structure due to its low atomic number of main elements and developed pores; in addition, the polar groups involved in the COF material can be combined with the hydroxyl groups in the porous carbon, and the water absorption rate of the host structure is reduced on the premise of improving the binding force between the host and the carrier; the acoustic volume-increasing material has a multi-level pore structure, which is conducive to air adsorption and desorption, and can significantly expand the virtual volume of devices such as speakers, has an acoustic volume-increasing effect and improves the effect of low-frequency performance, and can replace the existing zeolite material as a sound-absorbing material. In addition, the acoustic volume-increasing material provided by the present invention is itself a molding material, which does not need to be molded with the aid of an adhesive, improves the product's resistance to VOCs (volatile organic compounds), and has the characteristics of environmental protection and safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 Schematic diagram of the preparation process of the acoustic capacity-enhancing materials of Examples 1 to 3.
[0048] Figure 2 This is the SEM image of the carbonized coconut shell in Preparation Example 1.
[0049] Figure 3 This is the mesopore distribution diagram of the carbonized coconut shell in Preparation Example 1.
[0050] Figure 4 This is the macropore distribution diagram of the carbonized coconut shell in Preparation Example 1.
[0051] Figure 5 This is the SEM image of the acoustic capacity-enhancing material in Example 1.
[0052] Figure 6 This is the mesoporous diagram of the acoustic capacity-enhancing material in Example 1.
[0053] Figure 7 This is the macropore distribution diagram of the acoustic capacity enhancement material in Example 1.
[0054] Figure 8 The nitrogen adsorption-desorption curve and pore size distribution curve of the COF material of Comparative Example 1.
[0055] Fig. 9 This is the XRD pattern of the COF material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0056] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0057] The commercially available carbonized coconut shell used in the following experiments was produced by Huayu Zhengda, with an iodine value of 1000.
[0058] Preparation Example 1
[0059] This embodiment prepares a nearly spherical carbonized coconut shell, and the preparation method is as follows:
[0060] Commercially available carbonized coconut shell (also known as coconut shell charcoal) is screened with a sieve to obtain carbonized coconut shell with a particle size of 20-40 mesh; the carbonized coconut shell with a particle size of 20-40 mesh is transferred to a stainless steel ball mill for ball milling, and the friction and collision between the carbonized coconut shells are used during the ball milling process to remove the irregular edges and corners of the carbonized coconut shell particles to obtain ellipsoidal or spherical carbonized coconut shell particles; the ball-milled carbonized coconut shell is screened to obtain 30-40 mesh approximately spherical carbonized coconut shell particles, and then dried in a 60° C. blast oven for 12 hours; the dried nearly spherical carbonized coconut shell particles are placed in a room temperature dryer for standby use.
[0061] Preparation Example 2
[0062] This embodiment prepares a nearly spherical carbonized coconut shell, and the preparation method is as follows:
[0063] Commercially available carbonized coconut shell (also known as coconut shell charcoal) is screened with a sieve to obtain carbonized coconut shell with a particle size of 20-40 mesh; the carbonized coconut shell with a particle size of 20-40 mesh is transferred to a stainless steel ball mill for ball milling, and the friction and collision between the carbonized coconut shells are used during the ball milling process to remove the irregular edges and corners of the carbonized coconut shell particles to obtain ellipsoidal or spherical carbonized coconut shell particles; the ball-milled carbonized coconut shell is screened to obtain approximately spherical carbonized coconut shell particles with a particle size of 30-40 mesh, and then dried in a 60° C. blast oven for 12 hours;
[0064] The dried nearly spherical carbonized coconut shell particles are subjected to high-temperature nitrogen carbonization treatment, and the treatment conditions are flowing nitrogen at a constant temperature of 800°C for 4 hours; the high-temperature nitrogen carbonization treatment can remove the water molecules and small molecules adsorbed in the carbonized coconut shell, and at the same time, the uncarbonized tissue can be fully carbonized; the carbonized coconut shell obtained by the high-temperature nitrogen carbonization treatment is placed in a room temperature dryer for standby use.
[0065] Preparation Example 3
[0066] This embodiment prepares a nearly spherical hard carbon material, and the preparation method thereof is as follows:
[0067] Weigh 500.0g of lignite, place it in a 120℃ blast oven for baking and drying for 6 hours to remove moisture and volatile components; then place it in a high-temperature roasting furnace and carbonize it in a nitrogen environment at 1500℃ for 12 hours; after carbonization, crush it to obtain irregular hard carbon blocks, sieve the irregular hard carbon blocks to obtain hard carbon particles with a particle size of 20-40 mesh; transfer the 20-40 mesh hard carbon particles to a stainless steel ball mill for ball milling, and use the friction and collision between the hard carbon particles during the ball milling process to remove the irregular edges of the hard carbon particles to obtain ellipsoidal or spherical hard carbon particles; then sieve the ball-milled hard carbon particles to obtain 30-40 mesh approximately spherical hard carbon particles, and then dry them in a 60℃ blast oven for 12 hours. The dried hard carbon particles are placed in a room temperature dryer for standby use.
[0068] Example 1
[0069] This embodiment provides an acoustic capacity-enhancing material, such as Figure 1 As shown, the preparation method of the acoustic capacity increasing material comprises:
[0070] The experimental operations in this embodiment were all carried out in a vacuum glove box and a nitrogen environment, and a high borosilicate glass tube was used as a reaction container;
[0071] The specific experimental process includes:
[0072] 1. Weigh 200.0 mg of the carbonized coconut shell of Preparation Example 1 and place it in a borosilicate glass tube with an outer diameter of 20 mm and a wall thickness of 3 mm;
[0073] 2. Weigh 0.25 mmol (125.0 mg) of tetrakis (4-boronic acid phenyl) methane and place it in the borosilicate glass tube in step 1; then, add 0.625 mmol (83.5 mg) of n-butylsilanetriol and 4.2 mL of a mixed solution of toluene and dioxane as a solvent (the volume ratio of the two is 2:1) into the glass tube;
[0074] 3. Use liquid nitrogen (-77K) to flash freeze the mixed reaction raw materials in the glass tube, and pump the pressure to about 20Pa, and seal the glass tube at high temperature. The length of the glass tube after sealing is about 12cm; place the glass tube in a 30°C water bath for thawing and stirring. After stirring for 10 minutes, place the glass tube in a 120°C oven for crystallization for 3 days;
[0075] 4. After the crystallization is completed, the system after the reaction is centrifuged and washed by soaking in 50 ml of acetone. The centrifugation and washing operations are repeated twice, and then the acetone is removed by vacuuming to obtain the acoustic volume-enhancing material in which COF-202 resides.
[0076] In this embodiment, the mass proportion of COF material can be calculated by the mass change of carbonized coconut shell before and after crystallization. It is calculated that COF material accounts for 47.34%wt of the acoustic volume-enhancing material product. The crystallinity is calculated based on the XRD characterization results, and the crystallinity of COF-202 is 95%.
[0077] Example 2
[0078] This embodiment provides an acoustic capacity increasing material. The preparation method of this embodiment is basically the same as the preparation method of Example 1, except that 200.0 mg of carbonized coconut shell of Preparation Example 2 is used instead of 200.0 mg of carbonized coconut shell of Preparation Example 1. In this embodiment, the COF material in the acoustic capacity increasing material product accounts for 47.31%wt of the acoustic capacity increasing material product. The crystallinity is calculated based on the XRD characterization results, and the crystallinity of COF-202 is 96%.
[0079] Example 3
[0080] This embodiment provides an acoustic capacity-enhancing material. The preparation method of this embodiment is basically the same as the preparation method of Example 1, except that 200.0 mg of the carbonized coconut shell of Preparation Example 1 is replaced with 200.0 mg of the nearly spherical hard carbon of Preparation Example 3. In this embodiment, the COF material in the acoustic capacity-enhancing material product accounts for 47.54%wt of the acoustic capacity-enhancing material product. The crystallinity is calculated based on the XRD characterization results, and the crystallinity of COF-202 is 96%.
[0081] After testing, the density of the acoustic volume-increasing materials of Example 1, Example 2, and Example 3 is 0.692 g / cm 3 , 0.687g / cm 3 , 0.701g / cm 3 The specific surface areas of the acoustic volume-increasing materials of Example 1, Example 2, and Example 3 are 2763 m 2 / g, 2797m 2 / g, 2650m 2 / g.
[0082] Comparative Example 1
[0083] This comparative example provides a method for preparing COF-202 material, and the material preparation process (including the reagents and amounts used, and crystallization conditions) is the same as steps 1 to 4 in Example 1, but without the introduction of carbonized coconut shell. Figure 8 The BET test results show that the specific surface area of COF-202 material is 2643m 2 / g.
[0084] The porous carbon prepared in Preparation Example 1, Preparation Example 2, Preparation Example 3 and the porous carbon (carbonized coconut shell, hard carbon) used in Examples 1 to 3 all have mesopores and macropores, with the mesopore diameter being 2nm-50nm and the macropore diameter being 50nm-20μm.
[0085] Figure 1 Flow chart for preparing the parasitic acoustic capacity enhancement material for Examples 1 to 3.
[0086] Figure 2 This is the SEM image of the carbonized coconut shell in Preparation Example 1. It can be seen that after ball milling, the carbonized coconut shell has a nearly spherical appearance, and there are pore structures of mesopores and macropores on the surface.
[0087] Figure 3 This is the mesopore pore size distribution diagram of the carbonized coconut shell in Preparation Example 1. It can be seen that the mesopore size is obviously distributed in the range of 10nm-20nm.
[0088] Figure 4 This is the macropore size distribution diagram of the carbonized coconut shell in Preparation Example 1. It can be seen that the macropore size is obviously distributed in the range of 0.6μm-5μm.
[0089] The above data prove that the carbonized coconut shell of the preparation example has macropores and mesopores.
[0090] Figure 5 This is a SEM image of the parasitic acoustic capacity-enhancing material of Example 1. It can be seen that after the COF material enters the carbonized coconut shell, the mesopores and macropores on the surface of the carbonized coconut shell become smaller or disappear. This is because after the COF material crystallizes, it fills these pores, causing the mesopores and macropores on the surface of the carbonized coconut shell to become smaller or disappear.
[0091] Figure 6 This is a mesopore pore size distribution diagram of the acoustic volume-enhancing material in Example 1. It can be seen that the mesopore pore size is obviously distributed in the range of 2nm-20nm, and there is an ultra-microporous structure near the pore size of 1.6nm.
[0092] Figure 7 This is a macropore size distribution diagram of the acoustic volume-enhancing material in Example 1. It can be seen that the macropore size is obviously distributed in the range of 0.1 μm-5 μm.
[0093] Figure 8 The nitrogen adsorption-desorption curve and micropore size distribution curve of the crystallized product in Comparative Example 1, i.e., COF-202. Figure 8 It can be seen that the COF-202 material has a high specific surface area, which can reach 2560m 2 / g or above, and the pore size is about 1.1nm.
[0094] Fig. 9 The XRD diagram of the crystallized product in Comparative Example 1, i.e. COF-202, is shown in Figure 1. "COF-202" is the simulation result of the structural XRD in the literature. It can be seen that the COF material has a typical COF-202 topological structure and a high crystallinity of more than 90%.
[0095] Test Example 1
[0096] This test example provides the acoustic test results of the products prepared in Preparation Examples 1 to 3, Examples 1 to 3, and Comparative Example 1.
[0097] The samples to be tested are filled in a standard sound cavity for acoustic performance testing. The filling amount of each sample to be tested is 300 mg, the volume of the standard sound cavity is 1.0 cubic centimeter, and the structure of the standard sound cavity is the acoustic material test fixture assembly described in CN215072984U (invention name "An acoustic material test fixture assembly", application number 202120796674.2), and the full text of the patent is introduced here as a reference. The test signal is an analog program signal or pink noise signal specified in GB / T 12060.1 "Acoustic System Equipment Part 1: Overview". The test results are summarized in Table 1.
[0098] Table 1
[0099]
[0100] It can be seen from Table 1 that, compared with porous carbon alone and COF material alone, the porous carbon loaded with COF material as an acoustic volume-enhancing material in the present invention has a better effect of improving low frequencies, indicating that porous carbon and COF material can synergistically improve low-frequency effects.
[0101] Furthermore, compared with the acoustic volume-increasing material made from the carbonized coconut shell that has not been subjected to high-temperature treatment, the acoustic volume-increasing material prepared using the carbonized coconut shell that has been subjected to high-temperature treatment as a carrier has a better effect of improving low frequencies.
[0102] Test Example 2
[0103] This test example provides the test results of the mechanical strength of the products prepared in Preparation Examples 1 to 3 and Examples 1 to 3.
[0104] The test uses a microcomputer-controlled spring tension and compression testing machine as the test equipment; before the test, the test equipment range is adjusted to 0.005N~5N, and the accuracy is 0.001N; at room temperature, 5 samples of the same particle size are placed in the pressure plate to be tested, and the particle deformation is set to 5% of the particle size, and the descending speed is 5mm / min; after reaching the set deformation, the test is ended and the recorded data is saved; the compressive strength results are shown in Table 2.
[0105] Table 2
[0106] sample Preparation Example 1 Preparation Example 2 Preparation Example 3 Example 1 Example 2 Example 3 Test 1 1.052 1.063 1.088 1.452 1.561 1.564 Test 2 1.061 1.064 1.091 1.456 1.562 1.571 Test 3 1.060 1.057 1.087 1.458 1.565 1.567 Test 4 1.052 1.049 1.092 1.454 1.547 1.562 Test 5 1.049 1.055 1.090 1.449 1.553 1.553 Average value / N 1.055 1.058 1.090 1.454 1.558 1.563
[0107] As can be seen from Table 2, compared with the porous carbon material alone, the porous carbon loaded with COF material has higher mechanical strength. This is mainly because the COF material can play a filling and supporting role after entering the macropores or mesopores of the porous carbon, thereby improving the mechanical strength of the parasitic structure. The pores of the coconut shell charcoal treated with high-temperature nitrogen are more open, allowing more COF materials to be filled and embedded in the macropores of the coconut shell charcoal, and the mechanical strength is further improved.
[0108] Test Example 3
[0109] This test example provides the test results of the water absorption rate of the prepared products in Preparation Examples 1 to 3, Examples 1 to 3, and Comparative Example 1.
[0110] Before the test, weigh 2g±0.001g (M1) of the sample to be tested and spread it flat in a petri dish; adjust the test box to 85°C and the humidity to 85% RH for 24 hours, take out the sample, weigh its mass (M2) using an analytical balance and record it; calculate the water absorption rate of the sample to be tested based on the change in mass before and after the test. The test results are shown in Table 3.
[0111] Table 3
[0112]
[0113]
[0114] As can be seen from Table 3, compared with the porous carbon material alone, the porous carbon loaded with COF material has a lower water absorption rate. This is mainly because the COF material (Comparative Example 1) itself has a very low water absorption rate. After the COF material enters the macropores or mesopores of the porous carbon, in addition to the filling and supporting effect, it can also enhance the hydrophobicity of the surface of the porous carbon material. The water absorption rate of coconut shell charcoal (Preparation Example 2) treated with high-temperature nitrogen is higher than that of carbonized coconut shell (Preparation Example 1) that has not been treated with high temperature. This is mainly because, after being treated with high-temperature nitrogen, the adsorbed water molecules are removed, and the adsorption sites are exposed. Under high humidity, more water molecules will be adsorbed, and therefore, a higher water absorption rate is shown. After the introduction of COF material, the porous carbon of different materials shows a significant reduction in water absorption.
[0115] It can be seen from the above results that the present invention can combine the advantages of light weight, large air adsorption capacity and low water absorption of the carrier material with the advantages of regular pores and pore structure of the porous material by loading the COF material with three-dimensional pores into the porous carbon material, thereby systematically improving the acoustic low-frequency effect.
Claims
1. An acoustic volume-enhancing material, comprising a host carrier and a COF material, wherein the host carrier has a pore structure, and the pore structure includes mesopores and macropores; The COF material is loaded on and / or embedded in the pore structure of the host carrier; the COF material has three-dimensional pores, the pore diameter of the three-dimensional pores in the COF material is greater than or equal to 0.4 nm, and the three-dimensional pores are interconnected.
2. The acoustic volume enhancement material according to claim 1, wherein: The pore size of the mesopores of the host carrier is 2nm-50nm, and the pore size of the macropores of the host carrier is 50nm-20μm.
3. The acoustic volume-enhancing material according to claim 1 or 2, wherein: The host carrier includes a porous carbon material; Preferably, the porous carbon material comprises one or a combination of two or more of carbonized coconut shell, soft carbon, hard carbon, carbon molecular sieve, functionalized activated carbon, and alkaline-modified activated carbon; Preferably, the host carrier can withstand temperatures above 200°C.
4. The acoustic capacity-enhancing material according to claim 1, wherein: The COF material has micropores and / or mesopores.
5. The acoustic capacity-enhancing material according to claim 1, wherein: The COF material has three-dimensional channels connected by N building nodes, N≥4; Preferably, N is 4, 6 or 8; More preferably, the COF material includes one or a combination of two or more of COF-102, COF-103, COF-105, COF-108, COF-202, COF-300, COF-302, and COF-505.
6. The acoustic capacity-enhancing material according to claim 1, wherein: The mass ratio of the host carrier and the COF material is 4:1-1:4; Preferably, the mass ratio of the host carrier to the COF material is 2:1-1:
2.
7. The acoustic capacity-enhancing material according to claim 1, wherein: The compressive strength of the acoustic volume-increasing material is greater than or equal to 0.1N; Preferably, the compressive strength of the acoustic volume-enhancing material is greater than or equal to 1.4N.
8. The acoustic capacity-enhancing material according to claim 1, wherein: The density of the acoustic volume-increasing material is less than or equal to 0.8 g / cm 3 ; And / or, the specific surface area of the acoustic volume-increasing material is 2500-2900m 2 / g.
9. The acoustic capacity-enhancing material according to claim 1, wherein: The water absorption rate of the acoustic volume-increasing material is less than or equal to 5.0%.
10. A method for preparing the acoustic volume-enhancing material according to any one of claims 1 to 9, comprising: Immersing the host carrier in a solution of a COF material precursor for crystallization to obtain the acoustic volume-enhancing material; Wherein, the preparation method does not include a calcination step.
11. The preparation method according to claim 10, wherein: The host carrier is a pre-treated host carrier, and the pre-treatment process includes: treating the host carrier at a high temperature of 450° C.-800° C. in an inert atmosphere for more than 2 hours.
12. The preparation method according to claim 10, wherein: The COF material precursor includes a reagent having N connected building nodes, N≥4; Preferably, the COF material precursor includes a combination of two or more of tetrakis(4-boranophenyl)methane, n-butylsilanetriol, tetrakis(4-phenylamino)methane, 3,3',5,5'-tetraaldehyde biphenyl, [1,1:3,1-terphenyl]-3,3,5,5-tetraaldehyde, aminotetraphenylporphyrin, 2,3,6,7,14,15-hexaaldehyde phenyltriptycene, tetrakis(4-pinacolylphenyl)methane, tetrakis(4-boranophenyl)ethylene, and 3,3',5,5'-tetrakis(p-aminophenyl)-biphenyl.
13. A speaker module, wherein: The speaker module comprises the acoustic volume-enhancing material according to any one of claims 1 to 9; Preferably, the acoustic volume-increasing material is filled inside the speaker module; Preferably, a speaker is provided in the resonance cavity of the speaker module, and the acoustic volume increasing material is filled in the resonance cavity of the speaker module.
14. An electronic device comprising the speaker module according to claim 13; Preferably, the electronic device is a smart phone, a smart watch, a tablet computer, smart glasses, VR glasses, a smart speaker or a laptop computer; Preferably, the electronic device is provided with a sound output opening and a sound output channel, and the speaker module is acoustically coupled with the sound output opening through the sound output channel; More preferably, the speaker module is integrally formed with the electronic device; or, the electronic device further includes a casing, and the speaker module is disposed in an internal space formed by the casing.
Citation Information
Patent Citations
Acoustic material testing tool assembly
CN215072984U
Complex of carbon structure and covalent organic framework, preparation method therefor, and use thereof
CN107249730A
Carbon fiber-based sound absorbing material and preparation method thereof
CN109487434A
Acoustic reinforcing material block with layered pore channel structure as well as manufacturing method and application thereof
CN113024156A
Sound absorbing material and loudspeaker using same
CN113889062A
Cited By
Sound production device and electronic equipment
CN120499568A